Fertilizer Induced Amelioration of Nitrogen Fixation under Moisture Stress in Chickpea - Kumar, Rajiv; Kuhad, M S (Annals of Arid Zone, 2016)
The investigations were carried out on chickpea (Cieer arietinum L.)cultivar HC-I under pot culture with the objective to ameliorate the deleteriouseffects I of water stress using phosphorus and potassium alone and in combinationsat vegetative and reproductive stages. At both the stages, water stress-induced declinein relative water content (50-60%) decreased the nitrogen fixation in terms of ARA(40-47%) and nodule leghaemoglobin content (30-40%). Fertilizer applications considerablyimproved the RWC of leaf (upto 7%), N2-ase activity (3-14%) and leghaemoglobincontent of nodule (10-25%) under moisture deficit conditions. Phosphaticfertilizers proved better than potassium in ameliorating deleterious effects of waterstress on nitrogen fixation. Moreover, their interaction effects were still better.